Feasibility and optimal sizing analysis of hybrid PV/Wind powered seawater desalination system: A case study of four ports, Egypt - Ibrahim Elsayed; Hamdy Kanaan; Mohammed Mehanna (Heliyon)
This research aims to investigate A novel and complete system consists of hybrid renewable energy farm with high-energy-consuming seawater desalination in fourth locations in Egypt. This paper proposes fuzzy-based multi-criteria decision-making model for optimal sizing of a hybrid PV/Wind/Storage system to power the reverse osmosis (RO) desalination process in order to increase freshwater availability and meet the electric load requirement in selected area. Firstly, according to collected data and cost of electricity (COE) for various renewable energy resources, specific procedures to determining the optimal system design and optimal sizing (solar cell, wind turbine parameter and storage system units) are presented for selected site. The optimization based on finding the minimum net present cost (NPC) feeds the load demand and maintains the system's reliability. Secondly, the fuzzy analytic hierarchy process (FAHP) is implemented to select the optimal system considering ten performance criteria. The results show that the feasible design consists of 16 × 100-kWwind turbines, 4127-kW photovoltaic array, 153 PH245 storages and 710-kW converter. The feasible design has the optimal economic values among all criteria with least NPC, COE, and payback-period (PBP) of $9,08,046, 0.091$/kWh and 1.1 yr, respectively. Besides, it has a 100 % renewable energy system (RES).In contrast to recent studies that concentrated on incorporating renewable energy sources into desalination systems at specific Egyptian location. This approach is applied to different case studies with diverse renewable energy resources in multiple locations across Egypt, thus providing valuable insights for decision-makers tackling electricity and water shortages throughout Egypt. This research fills a gap in the optimization of hybrid renewable energy systems (HRES) by taking into account a variety of sustainability criteria, including technological feasibility, cost-effectiveness, emissions reduction, and socio-political considerations, in contrast to other studies that concentrated on single aims. Additionally, the research presents fuzzy logic and fuzzy-AHP and fuzzy-VIKOR decision-making techniques, enabling a comprehensive assessment of system design alternatives while taking uncertainties into consideration. In general, this study makes a significant addition to the field of renewable energy integration and gives decision-makers a framework for choosing the best answers to Egypt's water and electricity problems.